2007
DOI: 10.1007/s10096-007-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

Murine typhus in Cyprus: 21 paediatric cases

Abstract: The aim of this article is to present the manifestations of Rickettsia typhi infection in childhood. Twenty-one children under 15 years of age were hospitalised in the Department of Paediatrics of the Archbishop Makarios Hospital in Nicosia, Cyprus, from 2000 to 2006 with Rickettsia typhi infection. Ten of them were boys and 11 were girls. The median age was eight years (range four to 13 years). The most common clinical features were fever (100%) and rash (57%). Lymphadenopathy, usually cervical, was also a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
1
13
0
7
Order By: Relevance
“…Murine typhus, also known as endemic typhus, is a flea‐borne infectious disease with a worldwide distribution, caused by an obligate intracellular, gram‐negative microorganism, Rickettsia typhi [1]. The transmitting agent of R. typhi is the rat flea, Xenopsylla cheopis , although the cat flea, Ctenocephalides felis , has also been implicated [1–4]. Main reservoirs are rats, house mice, opossums, skunks and cats [1–3].…”
Section: Clinical Epidemiological and Laboratory Characteristics Ofmentioning
confidence: 99%
“…Murine typhus, also known as endemic typhus, is a flea‐borne infectious disease with a worldwide distribution, caused by an obligate intracellular, gram‐negative microorganism, Rickettsia typhi [1]. The transmitting agent of R. typhi is the rat flea, Xenopsylla cheopis , although the cat flea, Ctenocephalides felis , has also been implicated [1–4]. Main reservoirs are rats, house mice, opossums, skunks and cats [1–3].…”
Section: Clinical Epidemiological and Laboratory Characteristics Ofmentioning
confidence: 99%
“…The exact incidence of R.typhi infections in Cyprus was largely unknown, however, outbreaks of the infection in 1996 and 1997 [49], indicate that R.typhi infections remain a significant health problem in the island. More recently, a case series of 21 children with R. typhi infection was reported [54]. An epidemiological 9-year study of murine typhus in Cyprus has identified persistent endemic foci in the island [55].…”
Section: Rickettsia Species In Cyprus and Mechanisms Of Complement Evmentioning
confidence: 98%
“…Rising case numbers are reported from the US (Hawaii [27] and Texas [28, 29]) as well as from Southern Europe (e.g. Cyprus [30, 31], Greece [32], Spain [3336] including Canary Islands [37, 38]) and Portugal [39, 40]. Especially homeless people are at enhanced risk to acquire the infection.…”
Section: Introductionmentioning
confidence: 99%